Antidepressants in childhood psychopharmacotherapy - Tezcan, A.E.; Ulkeroglu, F.; Atmaca, M. (My University, 1996)
The indications for antidepressants use in children are often different from those in adults. But, the number of studies related to the efficacy and reliability of antidepressants which are being used for the treatment of childhood psychiatric disorders in very few. In this article; indications, side-effects, and dosages of antidepressants in childhood disorders are reviewed.
COCUK PSIKOFARMATERAPISINDE ANTIDEPRESANLAR
Keywords: amitriptyline; antidepressant agent; clomipramine; desipramine; fluoxetine; fluvoxamine; imipramine; moclobemide; monoamine oxidase inhibitor; nortriptyline; serotonin uptake inhibitor; tricyclic antidepressant agent; child; drug indication; human; mental disease; psychopharmacotherapy; review